The p53 codon 72 polymorphism (rs1042522) is associated with proliferative vitreoretinopathy: the Retina 4 Project. - Pastor-Idoate, S; Rodriguez-Hernández, I; Rojas, J; Fernández, I; García-Gutierrez, M; Ruiz-Moreno, J; Rocha-Sousa, A; Ramkissoon, Y; Harsum, S; Maclaren, R; Charteris, D; van Meurs, J; et al. (2013)
PURPOSE: To compare the distribution of a p53 gene polymorphism among European subjects undergoing primary retinal detachment (RD) surgery in relation to the development of proliferative vitreoretinopathy (PVR). DESIGN: Case-controlled gene association study conducted as a component of the Retina 4 Project (a European multicenter study). PARTICIPANTS AND CONTROLS: Five hundred fifty DNA samples, 134 with PVR secondary to primary RD and 416 with RD without PVR. METHODS: The p53 codon 72 polymorphism (rs1042522) was analyzed using allele-specific primer polymerase chain reaction. Proportions of genotypes and the proline (Pro-P) homozygote groups between subsamples from different countries were analyzed in 2 phases. In the first, subsamples from Spain and Portugal were analyzed. After significant results were found, samples from the United Kingdom (UK) and The Netherlands were analyzed (second phase). Genotypic and allelic frequencies were compared between cases and controls in the global sample. MAIN OUTCOME MEASURES: Single significant associations with PVR. RESULTS: A significant difference (P<0.05, Fisher exact test) was observed regarding the p53 genotype frequencies at codon 72 between the PVR cases and the non-PVR controls in Spain and Portugal (phase I), but not in the UK or The Netherlands (phase II). Analysis of Pro homozygote carriers between cases and controls revealed differences in Spain (29.01-42.18 and 2.29-10.20, respectively), Portugal (10.49-29.50 and 1.35-8.89, respectively), and The Netherlands (16.49-31.70 and 4.51-15.09, respectively), but no differences in the UK (7.68-18.1 and 4.85-13.94, respectively). The odds ratio of Pro carriers from Spain and Portugal together was 8.12 (95% confidence interval [CI], 3.72-17.69; P<0.05), whereas the odds ratio of Pro carriers from the UK and The Netherlands was 2.12 (95% CI, 0.96-4.68; P = 0.07). All control samples were in Hardy-Weinberg equilibrium. Considering the entire sample, significant differences were found in genotype frequencies between cases (RR, 30.59%; RP, 43.28%; PP, 26.11% [R = Arg; P = Pro]) and controls (RR, 39.66%; RP, 52.64%; PP, 7.69%) and in Pro homozygote carriers between controls (Pro homozygote 95% CI, 18.67-33.52) and cases (Pro homozygote 95% CI, 5.1-10.2). CONCLUSIONS: Results indicate that the Pro variant of p53 codon 72 polymorphism is associated with a higher risk of PVR developing after a primary RD. Further studies are necessary to understand the role of this polymorphism in the development of PVR.